Inventarisasi ektoparasit pada ikan konsumsi air tawar di Kecamatan Seruyan Hilir - Wahyuni Trisnawati; Sri Herlina (Fakultas Peternakan Universitas Kristen Palangka Raya, 2020)
The purpose of this study is to inventory the types of ectoparasites in fish consumption and to determine the level of prevalence, intensity, and dominance in fish consumption. This research was conducted for ± 3 (three) weeks in March starting from the second week to the fourth week. The method in examining samples is: Biopsy method on gills is done by taking a portion of gill tissue, scraping method which is by scraping mucus from fish skin. Research variables by calculating the value of Prevalence, Intensity, and Domination of some number of fish that are attacked by parasites. There are 4 types of parasites found in catfish (Pangasius pangasius), namely Oodinium sp, Dactylogyrus sp, Chilodonella sp, and Thaparocleidus sp. Each type of parasite was found to have infected organs such as gills (Oodinium sp, Dactylogyrus sp, Chilodonella sp, and Thaparocleidus sp), fins (Oodinium sp, and Chilodonella sp), mucus (Oodinium sp, Dactylogyrus sp, and Chilodonella sp). While there are 3 types of parasites found in Tilapia (Oreochromis niloticus), namely (Oodinium sp, Dactylogyrus sp, and Chilodonella sp. Each type of parasite was found to have infected organs such as gills (Oodinium sp, and Dactylogyrus sp), fins (Oodinium sp, and Chilodonella sp), mucus (Oodinium sp). Keywords : Inventory, Ectoparasites , Catfish, Tilapia.